Effects of pasture type on carcass and meat characteristics of kid goats - Smeti S.; Slimeni O.; Hajji H; Mekki I.; Mahouachi M.; Saadani F.; Atti N. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The aim of this experiment was to study the effect of the feeding system in two mountain areas from the Tunisian Northwest (Bahra and Ain Draham) on the carcass and meat characteristics of goats. In the region of Ain Draham, characterized by mountainous terrain and soil unsuitable for crops, goats grazed natural forests with dominance of woody species. While in the region of Bahra, grazing pasture is based on herbaceous and goats were supplemented with concentrate and hay. At the age of five months, ten goats from each region were slaughtered. Body weight at slaughter (SBW) of kids was affected by the pasture type (17.7 and 21.8 kg for Ain Draham and Bahra, respectively). Also, higher carcass weight and higher dressing percentage were recorded for goats from Bahra. Similarly, the skin, head and feet weights were higher for this group; these organs are strongly correlated to the SBW which was higher for Bahra region. However, chemical composition of goats’ meat (dry matter, proteins and lipids) was similar for goats from both regions. In conclusion, the concentrate supplementation to the herbaceous pasture resulted in higher SBW and carcass weight without effect on meat composition.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)